1997
DOI: 10.1099/0022-1317-78-9-2365
|View full text |Cite
|
Sign up to set email alerts
|

Baculoviruses contain a gene for the large subunit of ribonucleotide reductase.

Abstract: In the genomes of two baculoviruses, Spodoptera exigua and S. littoralis multicapsid nucleopolyhedroviruses (SeMNPV and SpliMNPV, respectively), an open reading frame (ORF) encoding the large subunit of ribonucleotide reductase (RR1) was identified. The predicted amino acid sequences of SeMNPV and SpliMNPV RR1 showed high homology to RR1 proteins from eukaryotes (ca. 70 % and 80 % similarity, respectively). The amino acid residues thought to be involved in catalytic function were conserved in the baculoviral R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
0
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 72 publications
(58 reference statements)
2
18
0
1
Order By: Relevance
“…Plasmid pSeEcoRI-2.2, containing the SeMNPV ubiquitin gene, was described previously by van Strien et al (1996). The fragments that hybridized to RB-33 were cloned and analysed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Plasmid pSeEcoRI-2.2, containing the SeMNPV ubiquitin gene, was described previously by van Strien et al (1996). The fragments that hybridized to RB-33 were cloned and analysed.…”
Section: Methodsmentioning
confidence: 99%
“…The SeMNPV-US isolate (Gelernter & Federici, 1986) and the AcMNPV E2 strain (Smith & Summers, 1978) were produced using S. exigua fourth instar larvae. Routine cell culture BFGE Homologous regions of Spodoptera exigua MNPV DNA Homologous regions of Spodoptera exigua MNPV DNA maintenance and AcMNPV and SeMNPV infection procedures were carried out according to published procedures (Summers & Smith, 1987 ;van Strien et al, 1996 ;Heldens et al, 1996). The SeMNPV plasmid and cosmid libraries were described previously (Heldens et al, 1996).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed physical map has recently been constructed (Heldens et al, 1996 b) and a few genes, e.g. coding for polyhedrin (van Strien et al, 1992), p10 (Zuidema et al, 1993) andubiquitin (van Strien et al, 1996), have been identified and characterized. Information about the identity and genetic location of cis-and trans-acting factors involved in the replication of SeMNPV DNA is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Further upstream, at position -230 and -251 nt, two characteristic early gene mRNA start sites (CAGT) were identified [27]. However, these putative start sites were not preceded by perfect TATA boxes as described by [28]. Downstream of the p26 ORF, two possible poly-A motifs were present at positions 41 and 51 nt relative to the putative stop codon TAA.…”
mentioning
confidence: 98%